Advances in breast cancer screening modalities and status of global screening programs. Issue 2 (25th May 2022) - Luo, Chenyu; Wang, Le; Zhang, Yuhan; Lu, Ming; Lu, Bin; Cai, Jie; Chen, Hongda; Dai, Min
Abstract: Breast cancer (BC) is the most prevalent malignancy worldwide, and a continued upward trend has been predicted in the coming decades. Screening in selected targeted populations, which is effective in reducing cancer‐related mortality, has been widely implemented in many countries. This review summarizes the advances in BC screening techniques, organized or opportunistic BC screening programs across different countries, and screening modalities recommended by different academic authorities. Mammography is the most widely used and effective technique for BC screening. Other complementary techniques include ultrasound, clinical breast examination, and magnetic resonance imaging. Novel screening tests, including digital breast tomosynthesis and liquid biopsies, are still under development. Globally, the implementation status of BC screening programs is uneven, which is reflected by differences in screening modes, techniques, and population coverage. The recommended optimal screening strategies varied according to the authoritative guidelines. The effectiveness of current screening programs is influenced by several factors, including low detection rate, high false‐positive rate, and unsatisfactory coverage and uptake rates. Exploration of accurate BC risk prediction models and the development of risk‐stratified screening strategies are highly warranted in future research. Key points: Mammography is the most widely used and most effective technique; other complementary techniques include ultrasound, clinical breast examination, and magnetic resonance imaging. Globally, the implementation status of breast cancer screening programs is uneven, which is reflected by differences in screening modes, techniques, and examination coverage. Combining effective risk prediction models and advanced screening techniques for risk‐stratified screening strategies may be the future direction.